TBRG4 silencing promotes progression of squamous cell carcinoma via regulation of CAV-1 expression and ROS formation - Wang, Junqi; Luo, Qing; Liu, Mingwei; Zhang, Chao; Jia, Yong; Tong, Ruifeng; Yang, Litao; Fu, Xiaowei (Cellular and Molecular Biology, 2020)
Esophageal cancer is the eighth most common cancer globally. Transforming growth factor Î² regulator 4 (TBRG4) and caveolin-1 (CAV-1) are implicated in tumor progression. The aim of this study was to investigate the expressions of TBRG4 and CAV-1 in esophageal squamous cell carcinoma (ESCC), and their relationship with reactive oxygen species (ROS) formation. Human ESCC cell lines (EC9706, TE-1, and Eca109), and normal esophageal mucosal cell line (Het-1) were used in this study. The silencing of TBRG4 and/or CAV-1 by sh-RNA or overexpression of CAV-1 after TBRG4 knockdown was used to assess ROS levels. The results showed that down-regulation of TBRG4 reduced CAV-1 expression, and promoted ROS formation in ESCCs (p < 0.01). However, CAV-1 overexpression increased the expression level of TBRG4, but decreased ROS level in EC9706 cells (p < 0.01). Similarly, TBRG4 knockdown significantly reduced CAV-1 expression, promoted ROS formation, and caused cell cycle arrest at G0/G1 phase (p < 0.01). Caveolin-1 (CAV-1) knockdown also promoted cell apoptosis, cellular ROS formation and cell cycle arrest at G0/G1 phase (p < 0.01). However, CAV-1 overexpression in sh-TBRG4-treated EC9706 cells significantly upregulated TBRG4 expression, but significantly reduced the level of ROS, and inhibited cell-cycle arrest and apoptosis (p < 0.01). The enhancements in bcl-2/bax ratio, cytochrome c expression, and ROS levels by sh-TBRG4 were significantly reversed by CAV-1 overexpression in EC9706 cells. These results show that the upregulated expression of TBRG4 or CAV-1 promotes ESCC progression via regulation of intracellular ROS levels and inhibition of mitochondria-dependent apoptotic pathway.